Indoor Positioning berbasis Wi-Fi untuk Notifikasi Pintar Berbasis Lokasi - Dareen Halim; Andre Rusli (Universitas Multimedia Nusantara, 2020)
Indoor localization has been researched widely in the recent two decades due to its wide range of applications such as navigation, elder care, advertising. This work presents a utilization of indoor positioning for a location-based smart notification purposed, deployed in a meeting room booking application. Our localization method is based on Wi-Fi fingerprint, tailored to our application needs to alleviate the drawback of its tedious offline phase. The initial implementation is done with limited number of recorded locations. The testing shows that the meeting room booking application works well, with the localization detecting user’s location correctly aside from when poor signal condition occurs.